Long-term stability of ready-to-use norepinephrine solution at 0.2 and 0.5 mg/mL. Issue Volume 27:Issue e1(2020) (6th February 2020) - Gilliot, Sixtine; Masse, Morgane; Genay, Stéphanie; Lannoy, Damien; Barthélémy, Christine; Décaudin, Bertrand; Odou, Pascal
Abstract : Objectives: Norepinephrine is a vasopressor frequently administered after dilution to treat hypotension and shocks in intensive care units. The stability of norepinephrine is known to be highly sensitive to storage conditions. Moreover, medication errors linked to the dilution step are frequent and may be deleterious for critically-ill patients, especially in intensive care units. This study aimed to evaluate the stability of ready-to-use diluted norepinephrine solutions prepared at two target concentrations (0.2 and 0.5 mg/mL), according to the summary of product characteristics, and stored for 365 days in two containers: AT-closed cyclic olefin copolymer vials, and polypropylene syringes. Methods: A fast reversed-phase liquid chromatography method coupled with an ultra-violet detector was developed to assess the chemical stability of norepinephrine solutions. Validation was conducted according to the linearity of the calibration ranges, selectivity, sensitivity, accuracy and precision. Dosage, sub-visible particle contamination, pH monitoring and sterility assays were performed. Chemical stability was maintained if the measured concentration respected the lower limit of 90% of the initial concentration. Containers were stored at −20±5°C, +5±3°C and +25±2°C with 60±5% relative humidity in a dark closed enclosure. Results: Stability was successfully maintained for every concentration and container tested when stored at −20±5°C and +5±3°C. In these storage conditions, particle contamination, pH monitoring and sterility assay respected the required criteria. Chemical degradation and colouring of solutions appeared before the end of the 1 year study period for most norepinephrine solutions stored at room temperature. Conclusions: Ready-to-use solutions containing 0.2 and 0.5 mg/mL norepinephrine in polypropylene syringes or cyclic olefin copolymer vials must be stored at refrigerated or frozen temperatures to obtain acceptable 1 year shelf-stability. Exposure to higher temperatures significantly decreases shelf-stability. Our study protocol for compounding polypropylene syringes and cyclic olefin copolymer vials containing norepinephrine is adapted to implementation in centralised intravenous additive services.